New Strait Times, 04 June 2009 (The New Straits Times Press (M) Bhd, 2009)
Three-time champion Tiger Woods has extra reason to be motivated for this week's Memorial tournament after being forced to watch last year's edition from the sidelines while recovering from knee surgery.